The Implementation of High School Local Content Learning in Babar Island - Julians Marantika; Tanwey Gerson Ratumanan; Effilina Kissiya (Faculty of Mathematics and Natural Sciences, University of Pattimura, 2019)
This study deals with the effort of obtaining information about aspects of practicality or implementation of lesson plans and local content textbooks, the quality of textbooks, and the responds of teachers and students toward local content and its application at the school in Babar island. The research was conducted at Babar State High School 1 using descriptive analytical method. Data was collected using observation and questionnaire techniques. Observations were made to obtain information related to the implementation of classroom learning. The questionnaire was used to explore teachers and students perspective about textbooks. The research results indicate that learning activities happened smoothly. The quality of the textbook used is quite good and has a good level of readability. The response of teachers and students to teaching books is highly positive. The teaching material provided is in accordance with the needs of the school, especially students. The enthusiasm of students is seen in the whole learning activities, both in face to face and in completing tasks (homework).